Minimal change disease and subacute interstitial nephritis in association with Edwardsiella tarda gastroenteritis following oyster consumption. (2021) - Bui, Albert; Cortese, Cherise; Libertin, Claudia R.; Porter, Ivan E.
Abstract: Edwardsiella tarda ( E. tarda ) is a gram-negative, facultatively anaerobic bacillus that is associated with gastroenteritis and a host of other extra-intestinal manifestations in humans. However, its impact on the kidneys is unclear. Most literature that has explored this association involves fish, marine life in which E. tarda inhabits. We report a rare case of a 72-year-old female who presented with an acute kidney injury (AKI) associated with newfound minimal change disease, subacute interstitial nephritis, and a severe E. tarda infection. Her clinical course resolved with antibiotics and glucocorticoids.